Pengaruh Pajak Daerah, Dana Alokasi Umum, Penggunaan Saldo Anggaran Lebih terhadap Belanja Daerah pada Kabupaten/Kota Sumatera Selatan dan Kepulauan Bangka Belitung - Dian Rahma Putri; Maria; Desi Indriasari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This This study aims to determine the effect of Local Taxes, General Allocation Funds and the Use of Excess Budget Balances on Regional Expenditures at the Regency / City Government of South Sumatra and Bangka Belitung Islands. This research data uses secondary data. This research data is obtained from the Regional Government Financial Report Audit Results (LHP LKPD) 2018 - 2022. The sample consisted of 17 Regency / City of South Sumatra and 7 Regency / City of Bangka Belitung so the total sample was 24 Regency / City samples within a period of 5 (Five) years (saturated sampling method). Multiple linear regression data analysis techniques using the help of the Statistical Product and Service solutions (SPSS) program version 26.00. The results of this study indicate that: (1) Local Tax partially has a positive and significant effect on Regional Expenditure (2) General Allocation Fund partially has a positive and significant effect on Regional Expenditure (3) Use of Excess Budget Balance partially has a positive and significant effect on Regional Expenditure (4) Local Taxes, General Allocation Fund, and Use of Excess Budget Balance simultaneously have a positive and significant effect on Regional Expenditure.